Formação em saúde e interprofissionalidade: contexto saúde da família - Barbosa, Ailma de Souza (2019)
Interprofessional Health Education consists of occasions when members of two or more professions learn together, interactively, with the explicit purpose of advancing the perspective of collaboration, as a prerogative for improving the quality of health care. Interprofessional education has relevance in the development of collaborative skills as pillars for effective teamwork, in the production of health services and promotion of care. Thus, it has been characterized as a tool to guide vocational training and as a strategy capable of overcoming the fragmentation of health work in the country. The objective was to develop an intervention based on the Methodology of Problematization and perspective of Education and Interprofessional Work, in a Family Health Unit of a capital of Northeast of Brazil. Exploratory study with a qualitative approach, based on the assumptions of action research, whose participants were: six professionals from a family health team; two teachers from one university and seven undergraduate nursing, dentistry and nutrition students, totaling fifteen people. The research took place in three stages, from November 2018 to May 2019. In the first stage, a diagnosis was made about both Interprofessional Education and collaborative practices in child care that already occurred in the health care system, through semi-structured interviews which were recorded, transcribed and analyzed according to Bardin's framework (2016). In the second stage, activities that were carried out through active methodologies were proposed, starting with an awareness workshop on education and interprofessional work in primary care, which triggered action planning processes in the health of children. In addition, subsequent activities were: collective planning, teamwork and intersectionality and two activities at the health care unity, in a total of five meetings, whose records of participant observation were made in a field diary. The third and last stage, evaluation of the meetings of stage two, was performed with the same 15 participants from the previous stages, through a Focus Group, whose speeches were recorded, transcribed, and analyzed by the method of thematic analysis Bardin (2016). The project was approved by the Research Ethics Committee of CCS / UFPB under number: 2,653,580. In this scenario there were initiatives that stimulate actions that permeate the Interprofessional Education, experienced by professionals, teachers and students. The reports express the collective desire to transform and value the practices of teaching and learning, qualify care in primary care and achieve effective collaborative work in the health team, capable of bringing about changes in vocational training. The intervention favored the (re) meeting between the subjects, the exchange of experience and collective learning, the (re) knowledge of roles in the team, as well as students and teachers. It was constituted as a dialogical and participatory space for the production of knowledge and practices in child health in primary care, from the perspective of Interprofessional Health Education and collaborative practices.